Reimagining and Contextualizing Fetal Weight Estimation. Issue 6 (November 2021) - Dreisbach, Caitlin
Abstract : Some women feel pressured to make decisions about timing and mode of birth based on estimated fetal weight. Our perinatal patient safety guest columnist, Dr. Dreisbach, presents the evidence for accuracy and utility of various methods of estimating fetal weight in the last few weeks of term pregnancy and how nurses can help pregnant women make informed decisions.